'Mechanism' Made Visible: Process and Perception in Henry Peach Robinson's Composite Photographs. Issue 2 (3rd April 2017) - Talbot, Emily
Abstract : This article analyses Henry Peach Robinson's method of making composite photographs in the context of widespread belief that the photographer's 'mechanism' was perceptible in the appearance of his prints. By examining Robinson's preparatory and darkroom procedures, as well as the photographer's extensive writing about his photographic practice, I suggest that composite photographs invited viewers to pay attention to process, and to take it into account in their evaluation of an image. This attitude challenged key tenets of academic art theory – the paradigm for nascent concepts of art in photography – by refusing to subordinate manual labour to that of the mind. While many nineteenth-century critics rejected Robinson's approach, the debates engendered by composite techniques reveal a persistent fascination with making that advanced photographic practice as a marker of artistic value.